KEMITRAAN PEMERINTAH SWASTA DALAM PENGANGKUTAN SAMPAH DI KOTA PEKANBARU TAHUN 2024 - Zulfa, Khusyairi; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research is motivated by the partnership between the Pekanbaru City Environment and Cleanliness Agency and the private sector in waste transportation, which aims to understand how the public-private partnership in waste transportation works, as well as to identify the factors hindering the public-private partnership in waste transportation using Leonhardt's theory of public-private partnership principles. This research uses a qualitative method with a descriptive approach, as well as primary and secondary data. The research results show that based on Leonhart's theory of public-private partnership principles, this partnership is functioning well in several indicators. On the transparency indicator, a mechanism for monthly routine reporting and data matching between both parties has been implemented. On the negotiation indicator, the initial agreement before the contract signing indicates that the negotiation process is proceeding well. The monitoring indicators have also been implemented with the presence of supervisory assistant teams, daily reports, and the use of global positioning system (GPS) technology. The indicator of role equality is functioning well, as evidenced by the clear division of tasks between the government and the private sector. However, on the commitment indicator, there are obstacles such as delayed payments to the private sector and the lack of facilities and infrastructure at the final disposal site (TPA), which hinder the waste transportation process. In addition, this study found several hindering factors in this partnership, including low public awareness of waste disposal times, the limited number of temporary waste disposal sites (TPS), the lack of heavy machinery at the final disposal site (TPA), and the presence of independent parties who collect waste in an uncoordinated manner. Keywords: Public-private partnership, Transportation, Waste